Traditional Chinese medicine classic herbal formula Xiaoqinglong decoction for acute exacerbation of chronic obstructive pulmonary disease: A systematic review protocol - Zhen, Gao (Medicine (Baltimore), 2018)
BACKGROUND: Xiaoqinglong decoction (XQLD) is 1 of the traditional Chinese medicine (TCM) classic herbal formula that is widely used in Asian for acute exacerbation of chronic obstructive pulmonary disease (AECOPD). In recent years, there has been increasing interest in the use of XQLD to treat COPD in China. So it is necessary to update the research and re-evaluate the efficacy and safety of XQLD to provide up-to-date evidence for COPD management. Therefore, we provide a protocol for a systematic review of XQLD for COPD. This protocol is described for a systematic review to investigate the beneficial effects and safety of XQLD for AECOPD. METHODS: A systematic literature search for article up to October 2018 will be performed in 3 Chinese electronic databases and 2 English electronic databases: Pubmed, Cochrane library, China national knowledge infrastructure (CNKI), Chinese science and technology periodical database (VIP), and Wanfang database. Inclusion criteria are randomized control trials of XQLD in treating AECOPD. The primary outcomes were total clinical efficacy rate, TCM symptom scores, TCM Symptom relief time. The secondary outcome was lung function, blood gas analysis, inflammatory cytokines and C-reactive protein (CRP). The summary results will be pooled using the random-effects model or fixed-effects model according to the heterogeneity of the included studies. RESULT: This systematic review will provide an evidence of XQLD for AECOPD, and will submit to a peer-reviewed journal for publication. CONCLUSION: The conclusion of this systematic review will provide evidence to judge whether XQLD is an effective intervention for AECOPD patients.